Disparities in Access to Artificial Intelligence and Their Impact on the Economy - Jondec Delgado, Cristhian Andre (2026)
This article examines disparities in access to artificial intelligence (AI) across different economic sectors and geographic regions, as well as their impact on job opportunities and business competitiveness. A systematic literature review reveals significant gaps in AI adoption, where larger corporations, better equipped in terms of technology and finances, tend to benefit more from these innovations. Conversely, small and medium-sized enterprises (SMEs) and low-income regions face barriers that limit their. Such inequalities adversely affect labor equity, as workers in professions with low AI adoption increasingly face the risks of job insecurity and unemployment. Public policies and international efforts are essential to leveling the playing field in this context. Significant digital asset distribution is crucial. Initiatives like the “Digital Europe Program” have the potential to address regional gaps by fostering digital and professional infrastructure growth. Likewise, international organizations such as UNESCO (2021) and the OECD (also in 2021) emphasize the importance of digital inclusion and acquiring related skills. Meanwhile, the World Economic Forum (2020) highlights the need for employees to be trained in technology-related topics.